Polskie placówki partyjne w USA 1945–1989. Analiza w świetle akt KC PZPR - Romański, Mirosław (Acta Universitatis Lodziensis. Folia Historica, 2014)
The article presents the subject matter of delegating the Polish political workers to the USA, within the period of the Polish People’s Republic, which has not been well known so far. It includes the general description of them and allows to familiarize with the mechanisms of these outposts functioning. Due to the that subject matter had not been developed wider in scientific periodicals, the article represents a contribution to the development of further research. There are not only the United States of America worth considering, but more than 80 countries where there were the outposts of the Polish Workers’ Party and the Polish United Workers’ Party. It appears from the text that activities of the Polish authorities were aimed at propagating the communist ideology, even in democratic countries. It was then one of the many elements of the policy imposing the conditions of the socialist state. The basis of the preliminary archival research of the article are the materials made by the Foreign Department of the Central Committee, kept in the Central Archives of Modern Records in Warsaw. The library with rich and extensive collections of records allowed to reconstruct the acting mechanisms of the discussed outposts.